Delistings in Europe and the Cost of Governance - Frederik Vinten; Steen Thomsen (Copenhagen Business School (CBS), Department of Economics, 2006)
We analyze delistings from European stock exchanges 1995-2005 as a function of market conditions, firm effects and governance regulation. We find that investor protection and corporate governance quality reduce the likelihood of going private, bankrupt or liquidated, but increase the likelihood of exit by merger or acquisition. Taking into consideration that corporate governance policy may be endogenously determined, the estimated policy effects turn out to be highly sensitive to model specification, but our best estimates produce qualitatively similar results. We conclude that the evidence is most consistent with efficient regulation: better protection of minority investors and higher corporate governance quality stimulates the market for corporate control (M&A) and reduces the incentive to go private. However, going private transactions have increased significantly while governance standards have been improved over the past decade, and we would not ignore the possibility that more regulation would lead to more delistings. For example, we find indications that the adoption of corporate governance codes and changes in the level of corporate governance indices increase the propensity to go private. It seems likely that increasing investor protection will at some point add more costs than benefits to companies and investors. Governments should therefore consider both costs and benefits of further regulation.
hdl:10398/7504
Keywords: G10; 330; delisting; public listing; mergers; acquisitions; bankruptcy; liquidation; going private; private equity; investor protection